The Low DIEP Flap: An Enhancement to the Abdominal Donor Site. Issue 1 (January 2016) - Eom, Jin Sup; Kim, Do Yeon; Kim, Eun Key; Lee, Taik Jong
Abstract : Background: A serious drawback of the deep inferior epigastric perforator (DIEP) flap is an abdominal scar that is too high. Because the umbilicus should be incorporated into the flap territory, lowering the scar is very difficult. This report describes a new DIEP flap design where the flap is placed in the lowermost part of the abdomen, well below the umbilicus, similar to a mini-abdominoplasty. Methods: The low DIEP flap was used only for cases with moderately sized breasts and reliable perforators way below the umbilicus. The flap's lower border was on the pubic rim and the upper border was usually located 4 to 6 cm below the umbilicus. The donor defect could be closed primarily without umbilicus detachment. Results: From May of 2014 to October of 2014, 47 consecutive cases underwent breast reconstruction with DIEP or superficial inferior epigastric artery flaps. Of these, 27 underwent low DIEP or low superficial inferior epigastric artery flap surgery. All breast reconstructions were successful except for one case of flap failure. When compared with the conventional DIEP flap, the weight of the low DIEP flap was smaller, and venous congestion was more common in the low DIEP flap cases. The abdominal scar left by the low DIEP flap was close to the pubic rim and could be concealed by underwear. Conclusions: The low DIEP flap is a new option for breast reconstruction that leaves a much more favorably located donor scar and umbilicus shape. However, planning with computed tomographic angiography is crucial to avoid venous insufficiency. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.